2023
DOI: 10.1111/head.14517
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of dual enkephalinase inhibition in a preclinical migraine model is mediated by activation of peripheral delta opioid receptors

Abstract: Objective The aim of this study was to evaluate whether elevating levels of enkephalin by inhibiting their degradation can attenuate stress‐induced migraine‐like behaviors in mice. Background Previous studies in animals have suggested the delta opioid receptor (DOR) as a novel migraine target. The primary endogenous ligands for DOR are enkephalins and their levels can be increased by pharmacological inhibition of enkephalinases; however, it is not clear whether enkephalinase inhibition can be efficacious in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 66 publications
1
6
0
Order By: Relevance
“…Indeed, previous studies using other pain models have reported that pretreatment with the peripherally acting opioid receptor antagonist naloxone methiodide reduced, albeit partially, the antinociceptive effect of PL37 36 . Furthermore, a recent study revealed that the analgesic effects of PL37 were mainly mediated by DOR activated in the peripheral nervous system 11 . This is consistent with previous findings showing that DOR may be a potential target for migraine therapy 37 .…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Indeed, previous studies using other pain models have reported that pretreatment with the peripherally acting opioid receptor antagonist naloxone methiodide reduced, albeit partially, the antinociceptive effect of PL37 36 . Furthermore, a recent study revealed that the analgesic effects of PL37 were mainly mediated by DOR activated in the peripheral nervous system 11 . This is consistent with previous findings showing that DOR may be a potential target for migraine therapy 37 .…”
Section: Discussionsupporting
confidence: 89%
“…The analgesic effect of PL37 has been demonstrated in various preclinical rodent models of pain, as oral administration of PL37 produced antinociception in the hot plate test 24 and in a murine model of bone cancer pain 25,26 . More recently, PL37 was found to be effective in two preclinical models of migraine 10,11 . Accordingly, we showed that oral administration of PL37 dose‐dependently inhibited ISDN‐induced cephalic MH in rats.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations